Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) − 7 .3 + 4. − 6 − 5 .3 + 2.3 = − 45 = 9 = 6
b) 3.6 + 2.9.5 − 18. − 4 7. − 7 + 12. − 7 + 7 = 18. 1 + 5 + 4 − 7 . 7 + 12 − 1 = 18.10 − 7.18 = − 10 7
5.3x = 5.34
=> x = 4
5.34 = 7.35 - 2.35
= 35 . (7 - 2)
= 5. 35
=> 3x = 35
=> x = 5
5^4-3/100=1/20
3^3+2+1/3*13=3^5/13
5.3^7-5/5.3^5-3=1
2^15+14+13/2^13+12+11=2^6
72x - 4.75 = 75.3
72x = 75.3 + 4.75
72x = 75.(3 + 4)
72x = 75.7
72x = 76
2x = 6
x = 6 : 2
x = 4
Xin lỗi bạn nha, cho mình sửa lại kết quả xíu
72x - 4.75 = 75.3
72x = 75.3 + 4.75
72x = 75.(3 + 4)
72x = 75.7
72x = 76
2x = 6
x = 6 : 2
x = 3
1; 5.22 + (\(x\) + 3) = 52
5.4 + (\(x\) + 3) = 25
20 + (\(x\) + 3) = 25
\(x\) + 3 = 25 - 20
\(x+3\) = 5
\(x\) = 5 - 3
\(x\) = 2
Vậy \(x=2\)
2; 23 + (\(x\) - 32) = 53 - 43
8 + (\(x\) - 9) = 125 - 64
8 + (\(x\) - 9) = 61
\(x\) - 9 = 61 - 8
\(x\) - 9 = 53
\(x\) = 53 + 9
\(x\) = 62
Vậy \(x\) = 62
c, \(5^{x+4}-3\cdot5^{x+3}=2\cdot5^{11}\)
\(\Leftrightarrow5^{x+3}\cdot5-3\cdot5^{x+3}=2\cdot5^{11}\)
\(\Leftrightarrow5^{x+3}\left(5-3\right)=2\cdot5^{11}\)
\(\Leftrightarrow5^{x+3}\cdot2=2\cdot5^{11}\)
\(\Leftrightarrow5^{x+3}=5^{11}\)
\(\Leftrightarrow x+3=11\)
\(\Leftrightarrow x=8\)
Vậy x = 8
d, \(2^x+2^{x+1}+2^{x+2}+2^{x+3}+2^{x+4}+2^{x+5}=480\)
\(\Leftrightarrow2^x\left(1+2+2^2+2^3+2^4+2^5\right)=480\)
\(\Leftrightarrow2^x\cdot63=480\)
\(\Leftrightarrow2^x=\frac{160}{21}\)
\(\Leftrightarrow x\approx2,93\)
72x - 4.75 = 75.3
72x = 75.3 + 4.75
72x = 75.(3 + 4)
72x = 75.7
72x = 76
2x = 6
x = 6 : 2
x = 4
47 – 7(x + 5) = 2^5.3
47 - 7x - 35 = 32. 3
12 - 7x = 96
7x = -84
x = -12